EVALUATION OF ANTIBACTERIAL, ANTITUMOR, ANTIOXIDANT ACTIVITIES AND PHENOLIC CONSTITUENTS OF FIELD-GROWN AND IN VITRO-GROWN LYSIMACHIA VULGARIS L. - Yildirim, Arzu Birinci; Guner, Birgul; Karakas, Fatma Pehlivan; Turker, Arzu Ucar (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Lysimachia vulgaris L. (Yellow loosestrife) is a medicinal plant in the family Myrsinaceae. It has been used in the treatment of fever, ulcer, diarrhea and wounds in folk medicine. It has also analgesic, expectorant, astringent and antiinflammatory activities. Two different sources of the plant (field-grown and in vitro-grown) were used to evaluate the biological activities (antibacterial, antitumor and antioxidant) of L. vulgaris. In vitro-grown plant materials were collected from L. vulgaris plants that were previously regenerated in our laboratory. Materials and Methods: Plant materials were extracted with water, ethanol and acetone. For antibacterial test, disc diffusion method and 10 different pathogenic bacteria were used. Antioxidant activity was indicated by using DPPH method. The total phenol amount by using Folin-Ciocaltaeu method and the total flavonoid amount by using aluminum chloride (AlCl3) colorimetric method were determined. Results: Generally, yellow loosestrife extracts demonstrated antibacterial activity against Gram-positive bacteria (Staphylococcus aureus, S. epidermidis and Streptococcus pyogenes). Strong antitumor activity of yellow loosestrife was observed via potato disc diffusion bioassay. Nine different phenolics were also determined and compared by using High-Performance Liquid Chromatography (HPLC). Conclusion: Future investigations should be focused on fractionation of the extracts to identify active components for biological activity.